Biodiesel Plants: Fueling the Sustainable Outlooks (IntechOpen, 2025)
Biodiesel Plants - Fueling the Sustainable Outlooks provides an approach to the crucial role biodiesel plants play in transitioning to a society less dependent on fossil fuels. Each chapter unveils a unique lens on the biodiesel production process, from the careful selection of feedstocks to the innovative technologies that are reshaping the industry’s future. With a focus on sustainability, it highlights technological advancements that reduce the environmental impacts of biodiesel production while promoting a greener, more resilient economy. Aimed at scientists, engineers, policymakers, and all those who envision a cleaner, more sustainable tomorrow, it offers valuable insights for anyone seeking to understand the future of renewable energy and its positive impact on the environment.